2019
DOI: 10.1080/17512786.2019.1696697
|View full text |Cite
|
Sign up to set email alerts
|

Medium-Specific Threats for Journalists: Examples from Philippines, Afghanistan and Venezuela

Abstract: Between 2012 and 2016, UNESCO registered 530 deaths of journalists. They also published a statistic showing that television journalists were the most killed, followed by print media, radio and online journalists. Hinted in this statistics is the need to understand the relationship between the medium through which and in which the journalists produce news and the threats and dangers posed to them. In this article, we discuss this interlinkage and call it medium-specific threats. As examples of this interlinkage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Research suggests that safety issues depend on context in geography and culture, but also journalistic practice and type of assignment (Garrido V., Høiby, & Mitra, 2019). Among the manuals and content descriptions we have analysed, the 'international' ones appear to have taken geography and environment well into consideration but put less emphasis on the type of story and information involved in the assignment.…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests that safety issues depend on context in geography and culture, but also journalistic practice and type of assignment (Garrido V., Høiby, & Mitra, 2019). Among the manuals and content descriptions we have analysed, the 'international' ones appear to have taken geography and environment well into consideration but put less emphasis on the type of story and information involved in the assignment.…”
Section: Introductionmentioning
confidence: 99%
“…The finding indicated that reducing conflict spots leads to reducing war and conflict prospects; it affects the quality of future journalism. Mitra et al (2019) reported in a study that working in conflict zones has led to the death of journalists. According to the study, a total of 530 journalists died during 2012-2016, as per UNESCO statistics.…”
Section: Literature Reviewmentioning
confidence: 99%